Improving Literacy for Students With Emotional and Behavioral Disorders: An Innovative Approach. (November 2022) - Benner, Gregory J.; Strycker, Lisa A.; Pennefather, Jordan; Smith, Jean Louise M.
Most students with emotional and behavioral disorders (EBD) have significant reading difficulties, but educators have few in-service professional learning opportunities geared to reading instruction for these students. The Integrated Literacy Study Group was developed as an online professional development program to prepare elementary teachers to meet the literacy needs of students with or at risk of EBD. In this study, the authors use a within-subjects design to evaluate the feasibility of the 10-week digital program with 13 elementary teachers. From pretest to posttest, teachers made statistically and educationally significant gains in knowledge of evidence-based social and emotional learning and reading strategies for students with EBD, as well as significant improvements in general teacher self-efficacy, reading self-efficacy, and social and emotional self-efficacy. Pretest-to-posttest change in teacher burnout and classroom management was educationally significant, but statistically nonsignificant. Most teachers perceived the program content as relevant to their needs and those of their students.